7. AMPLIFIKASI MEDIA TERIIADAP AKTIVITAS POLITIK DAN PERBURUHAN. - Yuliyanto, Muchamad (Faculty of Social and Political Sciences Diponegoro University, 2008)
Mass media as an instrument that has power to reality construction or deconstruction its, such as news paper eksposes about political activity since reformation era in Indonesia. The ability of media to frame political action or government policy indicates media as strategic subject in every political dynamics since election campaigne, making branded figure untul formatting public opinion. Besides that, recently media starts attention about labour movement in regional or local area. Media always ekspose about labour indicate its trend to support them as a part of economical dynamic in Indonesia. Media role as facilitator to agreement making together, labour-government-enterpreneur about UMK or UMR. So, media become public space in social transition to meet some aspects who has influence in their around.